171k views
0 votes
Which example illustrates the commutative property of addition for polynomials? 2x2 + 5x) = –(–2x2 – 5x) (2x2 + 5x) + 0 = (2x2 + 5x) (2x2 + 5x) + (4x2 – 4x) = 2x2 + 5x + 4x2 – 4x (2x2 + 5x) + (4x2 – 4x) = (4x2 – 4x) + (2x2 +

2 Answers

1 vote

Answer:

option D

Explanation:

(2x2 + 5x) + (4x2 – 4x) = (4x2 – 4x) + (2x2 + 5x)

User MichaelMilom
by
5.2k points
1 vote
Commutative is simply for example that:

A + B = B + A

The one that displays that property is:

(2x2 + 5x) + (4x2 – 4x) = (4x2 – 4x) + (2x2 + 5x)

The last one.
User Jduv
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.